PENGARUH MENGONSUMSI MINUMAN TUAK TERHADAP EROSI GIGI DI DESA MARIORIAJA KECAMATAN MARIORIWAWO KABUPATEN SOPPENG - R Ardian Priyambodo; Dahniar Dahniar (Media Kesehatan Gigi : Politeknik Kesehatan Makassar, 2019)
Palm wine from the palm is a typical drink of Marioriwawo, Soppeng. Bitter palm wine taken from fermented fruit of the sugar plant intercepts (Arenga pinnata) which is called sap. Excessive drinking palm wine can cause pathological effects in the oral cavity, because the Palm wine have a pH that is acidic that can affect the occurrence of dental erosion. The purpose of this study was to determine the effect of palm wine consumption on the occurrence of dental erosion. Methode of observation is descriptive analysis that aims to determine the influence of tuak drink to erosion of teeth.The results showed that bitterness of palm wine may result in tooth erosion. From a sample of 30 people, 17 people who had obtained dental erosion due to drinking bitter palm wine, and 13 people. Tooth erosion is most prevalent in men aged 21-25 years.Keyword               : Tooth erosion, palm wine